Impact of family practice continuity of care on unplanned hospital use for people with serious mental illness. (9th October 2019) - Ride, Jemimah; Kasteridis, Panagiotis; Gutacker, Nils; Doran, Tim; Rice, Nigel; Gravelle, Hugh; Kendrick, Tony; Mason, Anne; Goddard, Maria; Siddiqi, Najma; Gilbody, Simon; Williams, Rachael; et al.
Abstract: Objective: To investigate whether continuity of care in family practice reduces unplanned hospital use for people with serious mental illness (SMI). Data Sources: Linked administrative data on family practice and hospital utilization by people with SMI in England, 2007‐2014. Study Design: This observational cohort study used discrete‐time survival analysis to investigate the relationship between continuity of care in family practice and unplanned hospital use: emergency department (ED) presentations, and unplanned admissions for SMI and ambulatory care‐sensitive conditions (ACSC). The analysis distinguishes between relational continuity and management/ informational continuity (as captured by care plans) and accounts for unobserved confounding by examining deviation from long‐term averages. Data Collection/Extraction Methods: Individual‐level family practice administrative data linked to hospital administrative data. Principal Findings: Higher relational continuity was associated with 8‐11 percent lower risk of ED presentation and 23‐27 percent lower risk of ACSC admissions. Care plans were associated with 29 percent lower risk of ED presentation, 39 percent lower risk of SMI admissions, and 32 percent lower risk of ACSC admissions. Conclusions: Family practice continuity of care can reduce unplanned hospital use for physical and mental health of people with SMI.